Modifikasi Patient Satisfaction Questionnaire Short Form (PSQ-18) ke dalam Bahasa Indonesia - Vella Imaninda; Saifuddin Azwar (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This research purpose to develop a valid and reliable patient satisfaction tool. The modification procedures include: preparation, practice, and finalization. The result of modification is called Patient Satisfaction Questionnaire 2017 (KKP-2017). Aspects in KKP-2017 include: interpersonal manner, technical quality/professionalism behavior, accessibility/convenience, financial aspects, and physical environment. Data analysis includes content validity, item scale correlation and reliability. The result of content validity in 82 items cover three questionnaire formats which include KKP-2017 Format 40, Format 25, and Format 10. Items selection is considered by correlation coefficient > 0,3 that yield 40 items with reliability estimation 0,936, KKP-2017 Format 25 with reliability estimation 0.928 and KKP-Format 10 with reliability estimation 0.883. KKP-2017 can be used to measure the level of patient satisfaction in hospital services.